Undiagnosed status and associated factors of diabetes mellitus among adults living in eastern Ethiopia: Unmasking a silent killer of prevalence of diabetes mellitus - Ebisa Zerihun; Fikadu Abera; Guta Kune; Firaol Girma; Misgana Tesgera; Meseret Robi (Elsevier, 2024)
Background: The global prevalence of diabetes mellitus (DM) is increasing rapidly, with special concern for the entity silent or undiagnosed diabetes; those unaware of their condition. It is important to uncover the hidden extent of diabetes in order to identify diabetes-related problems early. Therefore, this study aimed to assess the prevalence of undiagnosed DM and associated factors in Eastern Ethiopia. Methods: A quantitative, community-based cross-sectional study was conducted among 609 adults not known to be diabetic from January 03 to February 23, 2023. A multi-stage sampling technique and a validated standardized instrument were used. Each participant was interviewed to collect socio-demographic and behavioral characteristics data. Anthropometric measurements were recorded. The fasting blood glucose (FBG) test was assessed by samples taken early in the morning, 8 h after night fasting. Undiagnosed DM was defined as not being diagnosed with Diabetes mellitus and an FBG level of ≥126 mg/dl. To identify factors associated with undiagnosed DM, logistics regression was used. The level of statistical significance was set at a value of p < 0.05. Results: The prevalence of undiagnosed diabetes mellitus was 8.64 % (95 % CI: 6.7-11.2). The multivariable analysis showed that sedentary behavior, family history of diabetes mellitus, current hypertension, and fruit consumption of fewer than three servings per week were independently associated with undiagnosed DM in studied participants. Conclusion: Almost one in eleven adults living in the study area had undiagnosed DM, and various associated factors identified were modifiable risk factors that could be useful in planning intervention measures for lifestyle modification.